The Influence of Experiential Marketing and Site Quality Influence Repurchase Intention: The Mediating Role of Customer Satisfaction - Duerasor, Nadia; Hermawan, Agus; Sopiah, Sopiah (Yayasan Sembilan Pemuda Indonesia, 2025)
This research examines the impact of experiential marketing and site quality on repurchase intention, with customer satisfaction serving as a mediating variable, among GrabFood users at the International Student Dormitory Edelweis, State University of Malang. In today’s digital era, online food ordering services have become essential to daily life, especially for students. This research employs a quantitative methodology utilizing a purposive sample procedure, including 111 respondents who are foreign students residing in the Edelweis Dormitory of the State University of Malang and users of the GrabFood application. The research conducted using SmartPLS 4 indicates that experiential marketing and site quality significantly enhance the satisfaction of customers. Neither experiential marketing nor site quality has a direct significant effect on repurchase intention. Customer satisfaction has a direct and significant impact on repurchase intention and serves as a strong mediator in the relationship among experiential marketing, site quality, and repurchase intention. The findings have significant implications for developing digital marketing strategies and enhancing the quality and services of food ordering applications.